Confined ZrO2 encapsulation over high capacity integrated 0.5Li[Ni0.5Mn1.5]O4·0.5[Li2MnO3·Li(Mn0.5Ni0.5)O2] cathode with enhanced electrochemical performance. (10th March 2016) - Lee, Gyung-Hwan; Choi, In Hyung; Oh, Mi Young; Park, Sung Ho; Nahm, Kee Suk; Aravindan, Vanchiappan; Lee, Yun-Sung
Abstract: Confined ZrO2 encapsulation over high capacity spinel-layer-layer structured 0.5Li[Ni0.5 Mn1.5 ]O4 ·0.5 [Li2 MnO3 ·Li(Mn0.5 Ni0.5 )O2 ] with various concentration by sol-gel process is reported. Presence of homogeneous ZrO2 layer is evident from the TEM studies. Various electrochemical studies such as optimization of ZrO2 concentration followed by rate performance, elevated temperature studies, and potential windows are also performed. Among the studies, 1 wt.% ZrO2 modification is found superior in 2 − 4.9 V vs. Li region compared to rest of the coating concentration and pristine compound. Cyclic voltammetry and impedance studies are also performed to understand the reaction mechanism and other electrochemical aspects.